2018
DOI: 10.1590/2175-8239-jbn-3807
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in atypical hemolytic uremic syndrome and scleroderma renal crisis: a critical analysis of pathophysiology

Abstract: Scleroderma is an autoimmune disease that affects multiple systems. While pathophysiologic mechanisms governing the development of scleroderma are relatively poorly understood, advances in our understanding of the complement system are clarifying the role of complement pathways in the development of atypical hemolytic uremic syndrome and scleroderma renal crisis. The abundant similarities in their presentation as well as the clinical course are raising the possibility of a common underlying pathogenesis. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…There is an established correlation between aHUS and membranoproliferative glomerulonephritis (C3 glomerulopathy) whose physiopathology involves genetic alterations in the regulatory proteins of the alternative complement pathway. Based on this finding, it has been hypothesized that both conditions could be the same entity with different phenotypes, varying from aHUS to C3 glomerulopathy (DDD or C3 glomerulonephritis) [ 4 , 14 , 23 , 25 ]. Hypocomplementemia was seen in 60% of the cases; however, this finding is not very sensitive or specific, being reported in only 30–50% of cases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an established correlation between aHUS and membranoproliferative glomerulonephritis (C3 glomerulopathy) whose physiopathology involves genetic alterations in the regulatory proteins of the alternative complement pathway. Based on this finding, it has been hypothesized that both conditions could be the same entity with different phenotypes, varying from aHUS to C3 glomerulopathy (DDD or C3 glomerulonephritis) [ 4 , 14 , 23 , 25 ]. Hypocomplementemia was seen in 60% of the cases; however, this finding is not very sensitive or specific, being reported in only 30–50% of cases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, it has been hypothesized that both conditions could be the same entity with different phenotypes, varying from aHUS to C3 glomerulopathy (DDD or C3 glomerulonephritis) [ 4 , 14 , 23 , 25 ]. Hypocomplementemia was seen in 60% of the cases; however, this finding is not very sensitive or specific, being reported in only 30–50% of cases [ 25 ]. Fakhouri et al reported 85% of cases with disorders in the complement regulatory proteins, being CFI mutation frequently documented [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 details the cases of SRC treated with eculizumab and the corresponding clinical response data. [18][19][20][21][22][23][24] In addition, this patient's genetic testing led to some equivocal findings of alleles not generally thought to be pathogenic. We cannot exclude a yet undescribed role for these genetic variants which affect susceptibility to complement amplifying and endothelium disruptive insults.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 details the cases of SRC treated with eculizumab and the corresponding clinical response data. 18 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation